Advances in computers. Volume 62, 2004 - Zelkowitz, Marvin V., 1945- (San Diego : Academic Press, 2004)
The series covers new developments in computer technology. Most chapters present an overview of a current subfield within computer science, with many citations, and often include new developments in the field by the authors of the individual chapters. Topics include hardware, software, theoretical underpinnings of computing, and novel applications of computers. This current volume emphasizes software engineering issues in the design of new software systems. The use of the new emerging agile methods is presented as well as timeboxing and model based software engineering (MBASE) as techniques to manage large scale developments. The book series is a valuable addition to university courses that emphasize the topics under discussion in that particular volume as well as belonging on the bookshelf of industrial practitioners who need to implement many of the technologies that are described. In-depth surveys and tutorials on new computer technology Well-known authors and researchers in the field Extensive bibliographies with most chapters Important chapters on new technologies for software development: agile methods, time boxing, MBASE.
Preface -- Contributors -- 1. An introduction to agile methods -- 2. The Timeboxing process model for iterative software development -- 3. A survey of empirical results on program slicing -- 4. Challenges in design and software infrastructure for ubiquitous computing applications -- 5. Introduction to MBASE (Model-Based [System] Architecting and Software Engineering) 6. Software quality estimation with case-based reasoning -- 7. Data management technology for decision support systems.
Includes bibliographical references and index.
Keywords: Electronic data processing; Computers; Electronic books